Effluent Quality Monitoring in Industrial Waste Water Treatment at PT. X - Sihombing, Patricia Bernadetha; Munandar, Andika (Sriwijaya Journal of Environment, 2023)
PT. X is an industry that produces waste from the main product manufacturing process and production residues. The waste produced is waste water. The purpose of carrying out this activity is to identify the sources and characteristics of waste water, know the waste water treatment system, know the results of waste water quality tests, and analyze the results of monitoring the quality of waste water. This activity is carried out by literature study, field observation, and primary data collection as well as secondary data. The results of this activity found that the source of waste water came from process waste water and cooling water. Data on the quality of waste water outlets used in 2022. The quality standards used are based on Minister of Environment and Forestry No. 19 of 2010, Governor Regulation No. 08 of 2012, and Palembang Mayor License No. 658.31 / IPLC / 0015 / DPMPTSP-PPL / 2020. Effluent monitoring at PT. X is tested monthly. The monitoring results of the effleunt liquid waste treatment at PT. X is observed to be still below the quality standards that have been set by safe funds to be discharged into water bodies.